2021
DOI: 10.3762/bjoc.17.32
|View full text |Cite
|
Sign up to set email alerts
|

CF3-substituted carbocations: underexploited intermediates with great potential in modern synthetic chemistry

Abstract: “The extraordinary instability of such an “ion” accounts for many of the peculiarities of organic reactions” – Franck C. Whitmore (1932). This statement from Whitmore came in a period where carbocations began to be considered as intermediates in reactions. Ninety years later, pointing at the strong knowledge acquired from the contributions of famous organic chemists, carbocations are very well known reaction intermediates. Among them, destabilized carbocations – carbocations substituted with electron-withdrawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 177 publications
0
15
0
Order By: Relevance
“…Organofluorine compounds have been widely used in pharmaceuticals, agrochemicals, and advanced materials due to their unique physicochemical properties . In this context, the selective introduction of fluoromethyl groups into organic molecules has attracted much attention over the past decades, such as trifluoromethylation, difluoromethylation, and monofluoromethylation . In particular, the difluoromethyl functionality (CF 2 H) is known as a bioisostere of OH and SH groups and as a lipophilic hydrogen bond donor, which has been frequently used in the design of new pharmaceuticals , and agrochemicals .…”
Section: Introductionmentioning
confidence: 99%
“…Organofluorine compounds have been widely used in pharmaceuticals, agrochemicals, and advanced materials due to their unique physicochemical properties . In this context, the selective introduction of fluoromethyl groups into organic molecules has attracted much attention over the past decades, such as trifluoromethylation, difluoromethylation, and monofluoromethylation . In particular, the difluoromethyl functionality (CF 2 H) is known as a bioisostere of OH and SH groups and as a lipophilic hydrogen bond donor, which has been frequently used in the design of new pharmaceuticals , and agrochemicals .…”
Section: Introductionmentioning
confidence: 99%
“…Superelectrophilic activation of organic compounds by the action of strong Brønsted and Lewis acids or acidic zeolites is one of the efficient methods for the synthesis of various polyfunctional substances, carbo-and hetero-cycles. [1][2][3][4][5][6][7][8] The activation by protonation (or coordination) of basic centers of organic molecules in Brønsted (or Lewis) acids leads to an intermediate generation of highly reactive multicharged cationic species. Thus, the superelectrophilic activation of alkenes conjugated with electron withdrawing groups, such as carbonyl ones, affords O,C-diprotonated species, which take part in Friedel-Crafts reactions with aromatic nucleophiles (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Inspired by those results, our plan was to use such a combination to enable the first catalytic intermolecular hydroarylation of α-(trifluoromethyl)styrenes with readily available arenes as nucleophilic partners, thereby rapidly assembling trifluoromethylated diarylalkanes via the formation of a α-(trifluoromethyl) carbenium. 17 We began our optimization studies with 1,1,1-trifluoromethylstyrene 1a as a model substrate in the presence of TfOH as 1). By using anisole 2a as an arene nucleophile, the target product 3 was obtained in 84% yield in the form of a separable 92:8 mixture of para/ortho regioisomers (Table 1, entry 1).…”
mentioning
confidence: 99%
“…While the hydroarylation of unactivated styrenes has been extensively investigated, the hydroarylation of highly electronically deactivated styrenes remains underdeveloped. However, we have recently demonstrated that the acidity of self-assembled hydrogen-bond clusters of hexafluoroisopropanol (HFIP) could be amplified through coordination to a Lewis acid (Ca­(NTf 2 ) 2 / n Bu 4 NPF 6 ) or a Brønsted acid (TfOH) to trigger cationic reactions using highly deactivated substrates. , Inspired by those results, our plan was to use such a combination to enable the first catalytic intermolecular hydroarylation of α-(trifluoromethyl)­styrenes with readily available arenes as nucleophilic partners, thereby rapidly assembling trifluoromethylated diarylalkanes via the formation of a α-(trifluoromethyl) carbenium …”
mentioning
confidence: 99%